The Effects of Different Rates of Behavior-Specific Praise in Secondary Classrooms. (April 2023) - O'Handley, Roderick D.; Olmi, D. Joe; Dufrene, Brad A.; Radley, Keith C.; Tingstrom, Daniel H.
Few studies examine the effects of behavior-specific praise (BSP) in secondary classrooms, and there is limited research examining the rate of BSP that is needed to improve classwide appropriately engaged behavior (AEB) and reduce disruptive behavior (DB). Using a multiple baseline design with an embedded A/B/C/A/C condition sequence counterbalanced across pairs of teachers, this study evaluated the effects of BSP delivered once per 2 min and once per 4 min, and the relative effects of both rates of BSP on classwide AEB and DB across four secondary classrooms. Based on visual analysis and non-overlap, using BSP once per 2 min produced large and immediate improvements in classwide AEB and DB. In contrast, using BSP once per 4 min had mixed effects on classwide AEB and DB. Overall, using BSP once per 2 min was superior to using BSP once per 4 min. Limitations, directions for future research, and practical implications are discussed.